2019
DOI: 10.1371/journal.pgen.1008461
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of helminth-specific immune responses in a wild population of Soay sheep (Ovis aries)

Abstract: Much of our knowledge of the drivers of immune variation, and how these responses vary over time, comes from humans, domesticated livestock or laboratory organisms. While the genetic basis of variation in immune responses have been investigated in these systems, there is a poor understanding of how genetic variation influences immunity in natural, untreated populations living in complex environments. Here, we examine the genetic architecture of variation in immune traits in the Soay sheep of St Kilda, an unman… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 107 publications
0
27
1
Order By: Relevance
“…Indeed, resistance is measured from FEC, whose distribution will be censored to 0 across a range of resistance levels, thereby hampering variance estimation. It is also possible that the selection applied to the pleiotropic gene networks underpinning the immune response to GIN infection (Lazzaro & Little, 2009 ; Sallé et al, 2012 ; Sparks et al, 2019 ) could yield asymmetric phenotypic expression upon selection. Additional rounds of divergence would be needed to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, resistance is measured from FEC, whose distribution will be censored to 0 across a range of resistance levels, thereby hampering variance estimation. It is also possible that the selection applied to the pleiotropic gene networks underpinning the immune response to GIN infection (Lazzaro & Little, 2009 ; Sallé et al, 2012 ; Sparks et al, 2019 ) could yield asymmetric phenotypic expression upon selection. Additional rounds of divergence would be needed to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding more resistant individuals is a promising alternative. Indeed, domestic (Bishop, 2012 ; Gruner et al, 2004 ; Woolaston, 1992 ) and wild populations (Gold et al, 2019 ; Smith et al, 1999 ; Sparks et al, 2019 ) often show heritable genetic variation for resistance to parasite infection that breeding programmes could exploit. This trait has a polygenic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Given that exposure to worms starts early, we would expect that all females would be sufficiently exposed to have developed an acquired immune response to strongyles by sexual maturity, despite exposure varying in time and space [ 19 ]. Given the high repeatability of antibody levels in adults, and positive associations with fitness and negative associations with FEC, we believe that these antibody levels reflect variation in the immune response rather than just differences in exposure in this population [ 22 , 35 ]. The substantial, consistent differences among mothers in neonatal antibody levels of their offspring (indicated by the large maternal effect) suggest maternal genotype and prior maternal environment may play an important role in driving the variation in maternal antibody transfer we observe in wild Soay sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminant colostrum, the majority of immunoglobulins are derived by transfer from the bloodstream [ 15 ]. Previously, it was shown that plasma anti-Tc IgA, IgE and IgG levels measured in August over 26 years are very repeatable in adult Soay sheep, with high correlations between measures in consecutive years [ 35 ]. As a result, we predicted that antibody levels in the previous August may reflect those in April of the following year.…”
Section: Methodsmentioning
confidence: 99%
“…However, in Soay sheep maternal effects on offspring parasite load appear, at least in part, to occur through maternal age and parasite load (Hayward et al, 2010). However, in that population and in some domestic sheep quantitative genetic analyses also support a contribution of maternal effects to nematode resistance (Coltman et al, 2001;Stear et al, 2001) and to helminth-specific immune responses in lambs (Sparks et al, 2019).…”
Section: Social Effects Tend Explain More Variation Than Genetic Factorsmentioning
confidence: 78%